2013
DOI: 10.1080/09291016.2012.704795
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype effects on general well-being and psychopathology levels in healthy young adults

Abstract: Variations in diurnal preferences for activity and sleep have long been classified as morning and evening chronotypes. Although morning and evening-types do not differ in sleep architecture, earlier studies have revealed the association between eveningness and psychopathology. However, most of these works had been conducted only with patient samples. Additionally, previous research has also discovered that morning-types have a healthier lifestyle than evening-types. Therefore, the aim of the present study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…Despite the high representativity of the study by Hsu et al (2012) with a total of 2919 participants and a participation rate of nearly 80%, it could be argued, that effects were confounded by the presence of physical or psychiatric disorders. Gulec et al (2013) explicitly accounted for these effects by rigorously medically diagnosing (mentally and physically) all potential participants with respect to all kinds of potential confounding medical, medication-related and psychological variables prior to inclusion in the study. Throughout this exclusion process, 220 undergraduates from the Ataturk University in Turkey (mean age 20.25 AE 4.03; 149 females ¼ 67.7%) were identified and took part in the study which focused on the relation between general mental and physical health, symptoms of psychopathology and chronotypes in healthy young adults (Gulec et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the high representativity of the study by Hsu et al (2012) with a total of 2919 participants and a participation rate of nearly 80%, it could be argued, that effects were confounded by the presence of physical or psychiatric disorders. Gulec et al (2013) explicitly accounted for these effects by rigorously medically diagnosing (mentally and physically) all potential participants with respect to all kinds of potential confounding medical, medication-related and psychological variables prior to inclusion in the study. Throughout this exclusion process, 220 undergraduates from the Ataturk University in Turkey (mean age 20.25 AE 4.03; 149 females ¼ 67.7%) were identified and took part in the study which focused on the relation between general mental and physical health, symptoms of psychopathology and chronotypes in healthy young adults (Gulec et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Gulec et al (2013) explicitly accounted for these effects by rigorously medically diagnosing (mentally and physically) all potential participants with respect to all kinds of potential confounding medical, medication-related and psychological variables prior to inclusion in the study. Throughout this exclusion process, 220 undergraduates from the Ataturk University in Turkey (mean age 20.25 AE 4.03; 149 females ¼ 67.7%) were identified and took part in the study which focused on the relation between general mental and physical health, symptoms of psychopathology and chronotypes in healthy young adults (Gulec et al, 2013). With regard to health status, the authors found in their study that more morning-oriented individuals had higher scores in a range of health-related measures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep is a crucial part of human existence, development and emotion regulation (Agargun, Boysan, & Hanoglu, 2004;Aydin et al, 2013;Boysan, 2016b;Boysan & Kagan, 2016;Gulec et al, 2011;Gulec et al, 2013;Minkel et al, 2012;Selvi et al, 2010;Siegel, 2005b). A primary function of sleep is to ensure cortically fully functioning during wakefulness (Siegel, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed to have both plasticity, a term referring to the 'absorb and readjust' capacity of sleepwake cycle in response to variability in personal and situational factors, and automaticity, a term referring to involuntary nature of well-adjusted schedule (Espie, 2002). Sleep has crucial implications that people with poor sleep may be subject to poor social, occupational and educational functioning (Abdel-Khalek, 2009;BaHammam, Al-Faris, Shaikh, & Saeed, 2006;Boysan, Güleç, Beşiroğlu, & Kalafat, 2010;Boysan & Kagan, 2016;Chiang, Arendt, Zheng, & Hanisch, 2014;Engle-Friedman & Riela, 2004;Gulec et al, 2013;Laakso et al, 1999;Lahl & Pietrowsky, 2006Martikainen et al, 2001;Schichl, Ziberi, Lahl, & Pietrowsky, 2011).…”
Section: Introductionmentioning
confidence: 99%